2022
DOI: 10.1093/jamiaopen/ooac082
|View full text |Cite
|
Sign up to set email alerts
|

Apps for Covid-19 in Germany: assessment using the German Mobile App Rating Scale

Abstract: Objective The purpose of this study is to provide an overview of apps to help control the spread of Covid-19 in Germany and rate them according to standardized instruments. Materials and Methods The Apple App Store and Google Play Store were systematically searched to identify apps dealing with Covid-19 in Germany. The German Mobile App Rating Scale (MARS-G) was used to independently assess app quality by two trained reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…The assessment of the apps resulted in an overall mean MARS score (objective only) of 3.62 points which could be interpreted as “acceptable” (score of 3) to “good” (score of 4). When compared to the current literature, the overall mean MARS score of this study is lower than those from other COVID-19-related app assessment studies [ 30 , 31 , 36 ] and other domain studies [ 22 , 25 , 28 ]. However, other literature had scores lower than 3.62 points [ 23 , 24 , 37 40 ].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The assessment of the apps resulted in an overall mean MARS score (objective only) of 3.62 points which could be interpreted as “acceptable” (score of 3) to “good” (score of 4). When compared to the current literature, the overall mean MARS score of this study is lower than those from other COVID-19-related app assessment studies [ 30 , 31 , 36 ] and other domain studies [ 22 , 25 , 28 ]. However, other literature had scores lower than 3.62 points [ 23 , 24 , 37 40 ].…”
Section: Discussioncontrasting
confidence: 79%
“…Lastly, the study found no significant correlation between the scores and the number of reviews and star ratings. The current literature on this is mixed – some studies found an association between MARS score (total or dimension scores) and the number of reviews and app star ratings [ 22 , 23 ] while others did not [ 30 ]. This could indicate that the number of reviews and the star rating of apps are probably not good indicators of the quality of an app in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review is limited by the timeframe of the database search and our narrow search strategy. Records published or updated after our search or research that did not meet our inclusion criteria were not considered [73]. It is possible that we thus unintentionally failed to include some relevant research.…”
Section: Limitationsmentioning
confidence: 99%
“…The project demonstrated that real-time data collection and analysis, facilitated by technology, could signi cantly augment traditional public health strategies [17][18][19]. This approach, akin to the digital surveillance and response systems deployed in other countries [20][21][22][23][24][25], exempli es how early implementation and proactive management can enhance pandemic tracking and containment efforts.…”
Section: Global Covid-19 Patterns Re Ected In the Hayati Project's Fi...mentioning
confidence: 99%